2021
DOI: 10.1093/ptj/pzab023
|View full text |Cite
|
Sign up to set email alerts
|

Parental Adherence to Home Activities in Early Intervention for Young Children With Delayed Motor Development

Abstract: Objective The purpose of this study was to investigate the relationship between characteristics of home activities and coaching practices with the adherence of parents of children with motor delays to home activities provided by physical therapists and occupational therapists in early intervention. Methods An online survey study was developed and distributed to physical therapists and occupational therapists across the United… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…Exercises that improve outcomes There were consistent ndings on the positive associations between parental perception of the bene ts and e cacy of exercise and HEPA in ve quantitative studies [22,30,33,37,40] and complemented by one qualitative study [42] which may support the generalisability of the ndings. In this case, it is thought that parents are highly motivated and hopeful when their children's conditions improve thanks to exercises performed.…”
Section: Amount Of Exercisementioning
confidence: 61%
“…Exercises that improve outcomes There were consistent ndings on the positive associations between parental perception of the bene ts and e cacy of exercise and HEPA in ve quantitative studies [22,30,33,37,40] and complemented by one qualitative study [42] which may support the generalisability of the ndings. In this case, it is thought that parents are highly motivated and hopeful when their children's conditions improve thanks to exercises performed.…”
Section: Amount Of Exercisementioning
confidence: 61%
“…The primary concern identified during the quality assessment was the universal use of convenience sampling across all studies, suggesting that participants might not accurately represent the target research population. Except for one study [ 32 ], none conducted power analyses or provided sample size estimates to justify their sample sizes. While there are no universal guidelines for determining the optimal sample size for multivariate analyses, a small sample size can undermine confidence in the findings [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…This observation aligns with a previous systematic review that found that all 61 identified self-report measures lacked psychometric validity [ 36 ]. The current review also noted that factors such as social support and self-efficacy were sometimes assessed using a single item derived from related validated scales, which may not effectively capture the target concepts [ 32 , 35 , 37 ]. Other research efforts have tried to mitigate these issues by developing new measures based on existing scales or theories in the scientific literature [ 22 , 35 , 37 ] or by pre-testing and piloting the scales.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The emotional stability gained by mothers after undergoing parenting coaching interventions will create a pleasant atmosphere, allowing them to prepare nutritious meals for their children (Yendi et al, 2017 ). Moreover, mothers will more readily adopt healthy eating habits that can become long-term family practices (Di Pasquale & Rivolta, 2018 ), thereby enhancing their children’s nutrition and influencing the quality of physical, cognitive, and motor development during childhood (Gmmash et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%